2009
DOI: 10.2967/jnumed.108.060723
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Characterization of a Series of 18F-Diaryl Sulfides (18F-2-(2′-((Dimethylamino)Methyl)-4′-(Fluoroalkoxy)Phenylthio)Benzenamine) for PET Imaging of the Serotonin Transporter

Abstract: PET of the serotonin transporter (SERT) in the brain is a useful tool for examining normal physiologic functions as well as disease states involving the serotonergic system. The goal of this study was to further develop and refine a series of 49-fluoroalkoxy-substituted, 18 F-radiolabeled SERT imaging agents. 2-(29-((Dimethylamino)methyl)-49-(4-18 F-fluorobutoxy)phenylthiol)-benzenamine (3) and 2-(29-((dimethylamino)methyl)-49-(5-18 Ffluoropentoxy)phenylthiol)benzenamine (4) were synthesized and evaluated alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 24 publications
2
13
0
Order By: Relevance
“…Compounds [ 18 F] 23 –[ 18 F] 31 were radiolabeled by 18 F − displacement of a mesylate group followed by reduction of the 2‐nitro group (Scheme ) . The fluoroalkyl ethers [ 18 F] 23 –[ 18 F] 26 were obtained in 6–35% rcy, >97% rcp, and SA of 15–170 GBq/µmol .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Compounds [ 18 F] 23 –[ 18 F] 31 were radiolabeled by 18 F − displacement of a mesylate group followed by reduction of the 2‐nitro group (Scheme ) . The fluoroalkyl ethers [ 18 F] 23 –[ 18 F] 26 were obtained in 6–35% rcy, >97% rcp, and SA of 15–170 GBq/µmol .…”
Section: Methodsmentioning
confidence: 99%
“…Compounds [ 18 F] 23 , [ 18 F] 24 , and [ 18 F] 27 –[ 18 F] 31 were initially evaluated by rat brain biodistribution studies that identified [ 18 F] 23 and [ 18 F] 24 as the most promising candidates on the basis of high brain uptake and fast washout . PET studies in rats further confirmed that [ 18 ] 23 and [ 18 ] 24 are the most promising of this series …”
Section: Methodsmentioning
confidence: 99%
“…Previously, [ 18 F]FPBM (Figure 3) was reported with having substitution on the phenyl ring B (compared with [ 18 F]4‐FADAM or [ 11 C]DASB) (Figure 3). [ 18 F]FPBM possesses high selective binding, high brain uptake (0.99% dose/g at 2 min post iv injection), and an excellent in vivo target‐to‐nontarget ratio (7.7 at 120 min post injection) . Labeling studies suggested that there is a tendency to produce a vinyl side product through an elimination reaction during the S N 2 substitution by the activated [ 18 F]fluoride ion .…”
Section: Introductionmentioning
confidence: 99%
“…Using the longer lived 18 F isotope ( t 1/2 = 110 min) compared to the shorter lived 11 C isotope ( t 1/2 = 20 min) would allow medical centers, lacking the necessary radiochemistry facilities for their own production of the radiotracer to have access to the radiotracer from off-site commercial sources. Recently, a new promising SERT radiotracer, [ 18 F]FPBM (Fig 1), has been shown to possess high affinity ( K i = 0.38 nM), good selectivity, high brain uptake (0.99 % dose/g at 2 min post-injection), and an excellent target to non-target ratio (7.7 at 120 min post-injection) through in vitro binding assays, in vivo biodistribution, ex vivo autoradiography, and PET imaging studies in normal rats [23-25]. This compound was also amenable to simple radiosynthesis with relatively good radiochemical yields, good specific activity, and high radiochemical purity [23-25].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a new promising SERT radiotracer, [ 18 F]FPBM (Fig 1), has been shown to possess high affinity ( K i = 0.38 nM), good selectivity, high brain uptake (0.99 % dose/g at 2 min post-injection), and an excellent target to non-target ratio (7.7 at 120 min post-injection) through in vitro binding assays, in vivo biodistribution, ex vivo autoradiography, and PET imaging studies in normal rats [23-25]. This compound was also amenable to simple radiosynthesis with relatively good radiochemical yields, good specific activity, and high radiochemical purity [23-25]. With these promising results, further studies were performed with [ 18 F]FPBM in a rat model of Parkinson’s disease induced by a 6-hydroxydopamine (6-OHDA) unilateral lesion of the nigrostriatal pathway.…”
Section: Introductionmentioning
confidence: 99%